Teams' innovation: getting there through knowledge sharing and absorptive capacity. Issue 1 (1st February 2017) - Curado, Carla; Oliveira, Mírian; Maçada, Antonio Carlos Gastaud; Nodari, Felipe
Abstract: This study addresses the contribution of knowledge sharing behaviour and absorptive capacity to innovation at team level. Although the hypotheses reflect the dominant literature, the study's novelty lies in the data collected from several industries in Portugal, avoiding possible industry bias. Relationships are tested outside sectors where traditionally team effects are studied, for example healthcare. Data were collected from 141 employees working in organizational teams, excluding top management teams, which are often the object of research addressing phenomena leading to innovation. There is no evidence in support of organizational size effect, team's geographic concentration effect or gender effect. However, team tenure duration is positively related to increased knowledge sharing, that is, recent teams do not share as much knowledge as older ones. Structural Equation Modelling was used to test the mediation effect of absorptive capacity between individual knowledge sharing behaviour and team innovation. Evidence in support of full mediation was found.